PENINGKATAN KEMAMPUAN KEPALA SEKOLAH DALAM MENYUSUN PROGRAM SUPERVISI AKADEMIK MELALUI SUPERVISI MANAJERIAL - Marhendri Marhendri (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The background of this research is that there are still principals in carrying out academic supervision without a well-structured and well-planned program, so that supervision is carried out if there will only be an assessment or accreditation. The purpose of this study was to improve the ability of principals to develop academic supervision programs through managerial supervision. This research was conducted in a primary school built by researchers in the District of Rakit Kulim, totaling 10 schools. The results of the study showed, in the first cycle, there were only 4 schools or 40% of principals who were able to arrange academic supervision programs properly and correctly, while 6 schools or 60% of principals had not been able to arrange the program properly. In the second cycle, the indicator of success in mentoring and managerial supervision in the second cycle was 80%. There are already 8 built primary schools that have completed the academic supervision program properly and correctly. While 2 elementary schools still have a number of programs that need to be improved, but have been able to show the results of the academic supervision program that was compiled. Can researchers conclude that by implementing managerial supervision can improve the ability of school principals in preparing academic supervision programs in primary schools built by Rakit Kulim District